Building Energy and Environment - Cao, Shi-Jie; Feng, Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the face of the formidable challenge posed by global climate change, the imperative to transform the building sector into a bastion of sustainable practices has never been more urgent. The Reprint of the Topic "Building Energy and Environment" is a compendium of cutting-edge research and innovative solutions that aims to propel the construction industry towards the goals of "carbon peaking" and "carbon neutrality".